Molecular survey of cattle ticks in Burundi: First report on the presence of the invasive Rhipicephalus microplus tick - Nyabongo, Lionel; Odongo, David O.; Milton, G.; Machuka, Eunice M.; Vudriko, P.; Pelle, Roger; Kanduma, E.G. (Public Library of Science, 2021)
A recent research study on prevalence of tick-borne pathogens in Burundi reported high prevalence and endemicity of Theileria parva, Anaplasma marginale and Babesia bigemina infections in cattle. Detailed information about tick species infesting animals, their distribution and genetic diversity in Burundi is outdated and limited. This study therefore assessed the prevalence and genetic diversity of tick species infesting cattle across agroecological zones (AEZs) in Burundi. A cross-sectional study on the occurrence of tick species was conducted in 24 districts of Burundi between October and December 2017. Differential identification and characterization of ticks collected was conducted using tick morphological keys and molecular tools (cox1 and 12S rRNA gene). Chi-square test was used to test for association between agroecological zones and the prevalence of tick species. Phylogenetic relationships were inferred using bayesian and maximum likelihood algorithms. A total of 483 ticks were collected from the five AEZs sampled. Six tick species comprising of Rhipicephalus appendiculatus, R. sanguineus, R. evertsi evertsi, R. microplus, R. decoloratus and Amblyomma variegatum were observed. Rhipicephalus appendiculatus were the most prevalent ticks (~45%). A total of 138 specimens (28%) were found to be Rhipicephalus microplus, suggesting an emerging threat for cattle farmers. Twelve R. appendiculatus cox1 haplotypes were obtained from 106 specimens that were sequenced. Two cox1 haplotypes of R. microplus which clustered into previously reported Clade A were observed. Rhipicephalus sanguineus and R. evertsi evertsi ticks, the vectors of numerous zoonotic pathogens, were collected from cattle, which constitute a high risk for public health. These findings reveal an overlapping distribution of tick vectors in Burundi. The design of ticks and tick-borne diseases control strategies should consider the distribution of different vectors across the AEZs particularly the presence of the highly invasive R. microplus tick in Burundi and the potential risk of introducing the pathogenic Babesia bovis.